Use of metakaolins from Eseka and Dibamba‐Cameroon as an optimization additive of CEM I Portland cement mortar - Arlin Bruno Tchamba; Jongie Placide Esunsen; Nguo Sylvestre Kanouo; Linda Lekuna Duna; Jérôme Dikwa; Michel Mbessa; Guy Molay Tchapga Gnamsi; Blaise Mimpouo; Charles Bwemba; George Elambo Nkeng (International Journal of Ceramic Engineering & Science, 2024)
Abstract The present study deals with two kaolins from Eseka and Dibamba‐Cameroon to determine their potential suitability as additive of CEM I 42.5R and to optimize the properties of cement in the sense to promote low‐carbon cement. X‐ray diffractometry was used to establish the mineralogical composition of two kaolins. X‐ray fluorescence was carried out to determine the chemical composition of kaolins and cement. Fine metakaolin powders obtained at 700°C were used as additive in CEM I 42.5R. Furthermore, consistency, setting time, water absorption, compressive and flexural test, and shrinkage test were evaluated. Scanning electron microscopy analysis was carried out to evaluate the microstructure variation. The substitution of CEM I with metakaolin resulted in a considerable increase in compressive and flexural strength from days 7 to 28 at optimum value. The compressive and flexural strengths at 28 days at optimum value of metakaolin increase to 52% and 44%, respectively, explaining the equilibrium oxides in the cement. The maximum values of strength with 20 wt.% MK1 and 30 wt.% MK2 at 7, 14, and 28 days appear in both cases when the ratio of SiO2/Al2O3 is between 2.8 and 2.9. The silica modulus and alumina modulus of cement–metakaolin improved when metakaolin was added. The properties of cement were optimized with a 52% increase in compressive strength at 28 days.